Al-Qur’an Pasca Pandemi, Studi Living Qur’an - Syarif Hidayat (STAI Terpadu Yogyakarta, 2021)
This study reveals how the Qur'an lives in society after the Covid-19 pandemic. The object of research in this paper focus on various kinds of community activities in an effort to revive the Koran after the Covid-19 pandemic. The data in this study were collected through observation and documentation techniques from various sources, both data from previous research, news, information in the field and others. tahsin, tahfidz, and studies of the interpretation of the Qur'an. Especially tadarus, there is an increasing trend compared to before the pandemic hit because of appeals from religious leaders, scholars, and even government officials to always read the Qur'an. The difference from before the pandemic was from a technical point of view of its implementation, most of the activities of reviving the Koran were carried out independently in their respective homes and carried out online, even if they had to do face-to-face activities, they must always pay attention to health protocols. Judging from the goal, most of the efforts to revive the Qur'an not only have the aim of getting closer to Allah SWT, but also aim to avoid the plague that is infecting most of the world's community, besides that the goal is also for those who are sick to get well soon from sick due to an outbreak that is becoming a pandemic and aims to end the epidemic soon.